comparative Analysis of Intrusion Detection Approaches - I., Ahmad (2010)
Information security is a serious issue especially in present age because a solo attack may cause a big harm in computer and network systems. Several intrusion detection approaches exist to tackle this critical issue but the problem is which one is more suitable in the field of intrusion. Further, these approaches are used in intrusion detection systems. Therefore, in this paper, we evaluated them so that a suitable approach may be advised to intrusion detection systems. This work describes the concepts, tool and methodology being used for evaluation analysis of different intrusion detection approaches using multi-criteria decision making technique. Moreover, conclusion on results is made and direction for future works is presented.